KETERHUBUNGAN PELANGI KUAT (src) PADA GRAF (1 Spl-(Cn )) UNTUK 3 ≤ n ≤ 10 - Ermita Rizki Albirri; Robiatul Adawiyah; Lela Nur Safrida; Reza Ambarwati (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2018)
Let G be nontrivial and connected graph. A total-coloured path is called as total-rainbow if its edges and internal vertices have distinct colours. For any two vertices u and v of G, a rainbow u−v geodesic in G is a rainbow u−v path of length d(u,v), where d(u,v) is the distance between u and v. The graph G is strongly rainbow connected if there exists a rainbow u−v geodesic for any two vertices u and v in G. The strong rainbow connection number of G, denoted src(G), is the minimum number of colors that are needed in order to make G strong rainbow connected. The result shows for 1 Spl - (Cn) and 3 ≥ n ≥ 10 there exist a coloring where diam(G) = rc(G) = src(G) ≤ m and diam(G) ≤ rc(G) ≤ src(G) ≤ m with m is the number of path 1 Spl - (Cn).